ENABLING NETWORK-CENTRIC MUSIC PERFORMANCE IN WIDE-AREA NETWORKS. - Kurtisi, Zefir; Xiaoyuan Gu; Wolf, Lars (Communications of the ACM, 2006)
The article focuses on the use of high speed Internet connections for music performance networking. The authors describe research into the use of computer networks for network-centric music performance (NMP). NMP will allow musicians to collaborate across computer networks, over distance, to rehearse or perform concerts. The article also mentions the Stanford SoundWire Project, which investigates NMP. The authors describe possible latency issues involved in NMP; they identify an acceptable network delay as anything under 30msec.